2017
DOI: 10.1155/2017/2676254
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Remission of an Untreated, MYC and BCL2 Coexpressing, High-Grade B-Cell Lymphoma: A Case Report and Literature Review

Abstract: Non-Hodgkin lymphomas (NHL) are a heterogeneous group of hematologic malignancies typically treated with multiagent chemotherapy. Rarely, spontaneous remissions can be observed, particularly in more indolent subtypes. The prognosis of aggressive NHL can be predicted using clinical and histopathologic factors. In aggressive B-cell NHL, the importance of MYC and BCL2 proto-oncogene coexpression (as assessed by immunohistochemistry) and high-grade histologic features are particularly noteworthy. We report a uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Spontaneous regression of tumors in the absence of treatment, especially with aggressive tumors, is rare. 8 Regression of PCDLBCL-LT in the absence of therapy is extremely rare, with limited reported cases in the medical literature. 9–13 Graham et al 9 reported a patient with histologically confirmed PCDLBCL-LT with a large, reticulated, erythematous-to-violaceous plaque of the leg that subsequently underwent spontaneous regression of the disease but recurred over a year after the initial presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous regression of tumors in the absence of treatment, especially with aggressive tumors, is rare. 8 Regression of PCDLBCL-LT in the absence of therapy is extremely rare, with limited reported cases in the medical literature. 9–13 Graham et al 9 reported a patient with histologically confirmed PCDLBCL-LT with a large, reticulated, erythematous-to-violaceous plaque of the leg that subsequently underwent spontaneous regression of the disease but recurred over a year after the initial presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism is still poorly understood and appears to be multifactorial [ 2 ]. Several hypotheses might explain the spontaneous remission of cancer, unified by the idea that the innate immune system is triggered and increases its ability to recognize and react on malignant cells [ 21 ]. Spontaneous remission occurs mostly in melanomas, hypernephromas and neuroblastomas, and might occasionally take place in lymphomas [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another report found 6 out of 44 cases of low grade lymphomas (13.6%) without previous treatment showed spontaneous remission [27]. There are some reports in the literature trying to provide explanations for this fascinating phenomenon [28,29], yet the mechanism for which is still largely not well understood. Two mechanisms have been proposed in the literature: The systemic immune response and the genetic mechanism.…”
Section: Discussionmentioning
confidence: 99%